Accrued Expense Tax Reform–Not Ready in 1954–Ready in 1969? - Brighton, Gerald D. (The Accounting Review, 1969)
Abstract The article reports on Accrued expense tax reform. The accounting profession was not ready in 1954 to govern its own conduct and had no effective means to re strain its clients, especially with regard to estimated expenses. Consequently, the opportunity to conform tax accounting more closely with general accounting was missed. Taxpayers and accountants over the years have kept the accrued expense and deferred income issues alive. There have been frequent court cases for individual items. Recently the American Institute of CPA's Committee on Federal Taxation formally revived these issues by including proposals for reenactment of Sections 432 and 462 in its recommendations to the U.S. Congress. The Statements on Responsibilities in Tax Practice, No. 4 of which was issued in October 1966, represent a very constructive program on the tax side of the picture. These, coupled with educational activities directed toward awareness of the ramifications of taxes, good rapport with the Internal Revenue Service and client education, needs to continue. Client education is certainly important because obviously practitioner accountants cannot carry the whole burden.